Upaya Meningkatkan Kepatenan Kebersihan Jalan Napas Pada Pasien Dengan Tuberkulosis Paru - Efendi, aan; , Arina Maliya, S. Kep. Ns., M.Si.Med (2017)
Pulmonary tuberculosis (TB) is a contagious disease caused by the pulmonary tuberculosis bacteria (Mycobacterium tuberculosis). Indonesian population who was diagnosed with pulmonary tuberculosis (TB) by health personnel in 2007 and 2013 did not differ (0.4%). Five provinces with the highest pulmonary tuberculosis are West Java, Papua, Jakarta, Gorontalo, Banten, and West Papua. Resident who was diagnosed with pulmonary tuberculosis by health workers, 44.4 percent treated with the drug program. Most of the germs of tuberculosis attacks the lungs, but can affect other organs of the body. The main symptoms of pulmonary tuberculosis are coughing for two weeks or more, cough accompanied by phlegm, sputum mixed with blood, difficulty breathing, weakness, loss of appetite, weight loss. One of the signs and symptoms of tuberculosis are coughing accompanied by phlegm and will lead to the ineffectiveness of the respiratory tract hygiene is not effective. The purpose of this research is to improve the patient's respiratory tract hygiene. So that no complications caused by the ineffectiveness of the respiratory tract hygiene is not effective. The research was conducted from February 20th to 24th 2017. The method used by the author was observation, interview, and documentation. The results of research are the ineffectiveness of cleanliness airway problems are related with the excessive accumulation of secretions or seputum on the respiratory tract. The interventions include assess vital signs, observation of breathing and respiratory tract circumstances, recommend that patients should rest, teach effective coughing techniques, collaboration with physicians in medicines administration.